(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper we investigate the Hyers-Ulam Stability of the abstract dynamic equation of the form where (The space of all bounded linear operators from a Banach space into itself) and f is rd-continous from a time scale to. Some examples illustrate the applicability of the main results.